PERAN PAGUYUBAN ORANGTUA SISWA DI KELAS VI SDN BANTALWATU TEPUS GUNUNGKIDUL - Lina Isnaini; Ana Fitrotun Nisa (Tuladha : Jurnal Pendidikan Dasar, 2023)
This study aims to describe the role of the parent’s association in class VI of SDN Bantalwatu, Tepus, Gunungkidul. The method used in this research qualitative method. Data collection techniques with documentation, interviews, and observation. While the data analysis technique used is the data analysis technique of the Miles & Huberman interactive model. The model includes data collection, data reduction, data presentation, and drawing conclusions. Validity test using technique and source triangulation. This resulted of this study indicate that the role of parents of class VI student at the SDN Bantalwatu include (1) participating in the facilities and infrastructure, namely providing educational material assistance. (2) participating in a moral form such as monitoring students in learning at home, contributing ideas, discussing student problems and attending various   activities at school (3) Participate in financial form, namely regular donations or activates that cannot be financed by the school.  The factors that encourage the participation of parents in motivating and the interest of parents to participate in education, there are Forums for participation in the form of association Forums and teacher attitude, while the inhibiting factors are different economic conditions, busy parents.